Cultural and intellectual property rights: a series of readers examining critical issues in contemporary Māori society - Pihama, Leonie; Smith, Cherryl Waerea-i-te-Rangi (Moko Productions/IRI, 1997)
Keywords: civil Rights; colonisation; intellectual property; print only; treaty claims

The greatest good for the greatest number?: Rangatiratanga and the reform of local government 1987-1990 - Crengle, Diane (1993)
Keywords: crown law; local government; not sure if maori; print only; resource management act 1991; thesis; tiriti o waitangi/treaty of waitangi

Discourses and silences: indigenous peoples, risks and resistance - Cant, Garth; Goodall, Anake; Inns, Justine (Dept. of Geography, University of Canterbury, 2005)
Keywords: civil Rights; human rights; iwi taketake; print only; unsure if maori

Māori property rights and the foreshore and seabed: the last frontier - Charters, Claire; Erueti, Andrew (Victoria University Press, 2007)
"In this era of indigenous peoples' rights recognition, states around the globe are faced with reconciling the pre-existing, inherent rights of indigenous peoples with those held and asserted by the state. This fact was brought into sharp focus in New Zealand by the Court of Appeal decision of Ngati Apa." "This collection of essays does not aim to be an exhaustive treatment of the legal issues raised by Ngati Apa and the Foreshore and Seabed Act 2004 (the FSA). It does, however, address many of the most salient."–BOOK JACKET.
Keywords: iwi taketake; kaitiakitanga; law; legislation; new zealand foreshore and seabed act 2004; print only; seashore; shorelines; takutai moana; tikanga | indigenous law; treaty claims; ture whenua

Conversations about indigenous rights: the UN Declaration on the Rights of Indigenous Peoples and Aotearoa New Zealand - Katene, Selwyn; Taonui, Rawiri (Massey University Press, 2018)
The UN declaration on the Rights of Indigenous Peoples is a deeply significant document. In 2007, then UN Secretary-General Ban Ki-moon described its signing as an "historic moment when UN Member States and indigenous peoples reconciled with their painful histories and resolved to move forward together on the path of human rights, justice and development for all". This book reflects on the tenth anniversary of the UN General Assembly's adoption of the Declaration and examines its relevance in New Zealand. It shows the strong alignment between the Treaty of Waitangi and the Declaration, and examines how the Declaration assists the interpretation and application of Treaty principles of partnership, protection and participation. Starting from a range of viewpoints and disciplines, the authors agree that in Aotearoa New Zealand the journey to full implementation is now well underway, but warn that greater political leadership, willpower, resources and a stronger government commitment is needed.
Keywords: UNDRIP; civil Rights; international relations; print only; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi